The effectiveness of garlic, black turmeric, and red betel vine solutions to maintain scalp hygiene (pediculicide efficacy test toward head lice) - Samiasih, Amin; Dianingsih, Ayu; Ferdisa, Richa Jannet; Wati, Fitria; Hartiti, Tri; Ernawati, Ernawati; Yanto, Arief (South East Asia Nursing Research, 2020)
Head lice (Pediculosis humanus capitis) is a parasite sticking on the scalp and in between the hair. It lives by laying its eggs on some strands of hair and sucking blood from the scalp, which results in itching, inflammation, restless sleep, and concentration degradation. Lice could also lower self-esteem. The infection may also lead to anaemia, which affects the learning pattern and cognitive function of children. However, the use of chemical insecticide may have a harmful effect. Therefore, this research tested three natural ingredients, namely garlic, black turmeric, and red betel vine, as the pediculicide. This research was aimed to find safe, natural ingredients to eliminate head lice while maintaining personal hygiene. It was an experimental research with Randomized Posttest Only Control Grup Design. This research's subject was 28 lice, which were grouped into seven treatments with four lice in each group. The seven treatments included the treatment by spraying garlic, black turmeric, and red betel vine solution. The concentration of those natural ingredients was determined at 8% and 16%. The control group was sprayed by using water. The finding showed the significance of black turmeric (p-value 0.000), garlic (p-value 0.000), and red betel vine (p-value 0.001) as the effective pediculicide. The effective concentration as pediculicide was a 16% solution.